2016
DOI: 10.1007/s10964-016-0422-5
|View full text |Cite
|
Sign up to set email alerts
|

Skin Conductance Level Reactivity Moderates the Association Between Parental Psychological Control and Relational Aggression in Emerging Adulthood

Abstract: When studying factors that may heighten risk for relational aggression in youth, it is important to consider characteristics of both the individual and their environment. This research examined the associations between parental psychological control and reactive and proactive relational aggression in emerging adults in college. Given that sympathetic nervous system (SNS) activation may underlie differences between reactive and proactive aggression and has been shown to moderate the effects of parenting on yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 105 publications
0
20
0
Order By: Relevance
“…The results of the current study are similar to those of previous studies indicating that child development is conditional upon the interaction between the environment and children's physiological characteristics. Past research has supported this premise for numerous environmental characteristics and child outcomes, and across various child developmental periods: infancy (Feldman, 2007;Feldman & Eidelman, 2007), toddlerhood (Eisenberg et al, 2012), childhood (El-Sheikh, Harger, & Whitson, 2001;Obradović et al, 2010), adolescence (Rousseau et al, 2014), and emerging adulthood (Wagner & Abaied, 2016). Nevertheless, empirical research on the moderating role of child physiological activity for positive socialization processes is rare (Pluess & Belsky, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study are similar to those of previous studies indicating that child development is conditional upon the interaction between the environment and children's physiological characteristics. Past research has supported this premise for numerous environmental characteristics and child outcomes, and across various child developmental periods: infancy (Feldman, 2007;Feldman & Eidelman, 2007), toddlerhood (Eisenberg et al, 2012), childhood (El-Sheikh, Harger, & Whitson, 2001;Obradović et al, 2010), adolescence (Rousseau et al, 2014), and emerging adulthood (Wagner & Abaied, 2016). Nevertheless, empirical research on the moderating role of child physiological activity for positive socialization processes is rare (Pluess & Belsky, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this theory, heightened SCR to peer stress positively predicts reactive but not proactive aggression among children (Hubbard et al, ) and young adults (Murray‐Close et al, ; Wagner & Abaied, ). In terms of PNS functioning, low resting RSA positively predicts reactive but not proactive aggression in children (Xu et al, ).…”
Section: Psychophysiology Of Reactive and Proactive Aggressionmentioning
confidence: 91%
“…In terms of PNS functioning, low resting RSA positively predicts reactive but not proactive aggression in children (Xu et al, ). In contrast, low resting heart rate in Chinese youth (Raine, Fung, Portnoy, Choy, & Spring, ), as well as blunted SCR to peer stress in young adults (Murray‐Close et al, ; Wagner & Abaied, ), have been linked with proactive but not reactive aggression. Furthermore, young adults who exhibit RSA withdrawal concordant with low SCR are at highest risk for self‐reported proactive aggression (Murray‐Close et al, ).…”
Section: Psychophysiology Of Reactive and Proactive Aggressionmentioning
confidence: 99%
“…Studies showed that lower (Gregson, Tu, & Erath, 2014;Hinnant, Erath, Tu, & El-Sheikh, 2016;McQuade & Breaux, 2017;Waters, Boyce, Eskenazi, & Alkon, 2016) as well as higher (Cummings, El-Sheikh, Kouros, & Keller, 2007;Hinnant et al, 2016) SNS reactivity functions as a vulnerability factor for developing ASB in the context of higher social risk. Interaction effects were found between SNS reactivity and familial (El-Sheikh, 2005a;Wagner & Abaied, 2016) as well as peer (Gregson et al, 2014;Hinnant et al, 2016; Murray-Close, 2011) related social risk factors. For example, Hinnant et al (2016) found that the association between affiliation with deviant peers and ASB is stronger among adolescents with higher as well as lower SNS reactivity.…”
Section: Sns Functioningmentioning
confidence: 99%